2017
DOI: 10.3168/jds.2016-11840
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance in prepubertal dairy heifers allocated in continuous competitive dyads: Effects on body growth, metabolic status, and reproductive development

Abstract: The objective of this study was to compare the body weight (BW) and size, metabolic status, and reproductive development of dominant and subordinate prepubertal dairy heifers allocated in competitive dyads. Sixteen Holstein and Jersey × Holstein prepubertal heifers (means ± SEM; 250.8 ± 9.8 d; 208.5 ± 13.9 kg of BW) were assigned to 8 homogeneous dyads according to breed, age, and BW. Dyads were housed in pens separated 1 m from each other during 120 d, receiving a total mixed ration on a 5% restriction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…licular growth can be hypothesized. For instance, Fiol et al (2017) compared prepubertal Holstein heifers according to their social behavior and reported that relative to subordinate heifers, dominant heifers achieved a greater BW, had greater circulating glucose, greater number of follicles, greater maximum follicle diameter, and achieved puberty earlier, likely because they had more frequent access to feed due to their dominant demeanor. Furthermore, decreased circulating insulin and IGF-1, induced by reducing the dietary energy contents in the postweaning diet (Armstrong et al, 2001) or by feed restriction (Lents et al, 2013), were negatively associated with the dominant follicle size in cycling heifers (Armstrong et al, 2001;Lents et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…licular growth can be hypothesized. For instance, Fiol et al (2017) compared prepubertal Holstein heifers according to their social behavior and reported that relative to subordinate heifers, dominant heifers achieved a greater BW, had greater circulating glucose, greater number of follicles, greater maximum follicle diameter, and achieved puberty earlier, likely because they had more frequent access to feed due to their dominant demeanor. Furthermore, decreased circulating insulin and IGF-1, induced by reducing the dietary energy contents in the postweaning diet (Armstrong et al, 2001) or by feed restriction (Lents et al, 2013), were negatively associated with the dominant follicle size in cycling heifers (Armstrong et al, 2001;Lents et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects appear to be acute and are not likely to robustly affect production. Social dominance has also been shown to affect feeding behavior, growth rate, metabolic status, and age at onset of puberty (Fiol et al, 2017).…”
Section: Social Stressmentioning
confidence: 99%
“…Since no differences in LW at puberty occurred between HSR vs. LSR females, such an increased glucose level may explain the amplified productive and reproductive outcomes shown by the HSR-group [36]. Based on these findings [8,36], such an increased glucose level favoring the HSR-females may have been positively related to increases in LW, augmenting in turn both metabolic status and reproductive function in a GnRH-LH dependent fashion, a possible scenario occurring in the HSR-goats of this study. In this respect, although diverse neural and hormonal cues are involved as drivers of the hypothalamic-pituitary-gonadal axis, the common and undisputable initiator involved the activation of GnRH neurons [15].…”
Section: Discussionmentioning
confidence: 98%